Moments before the flood - De Keyzer, Carl (Houten : Lannoo, 2012)
For four years, Carl De Keyzer travelled four months a year along the coasts of Europe, from the far north to the deep south. He photographed alienating landscapes, desolate beaches, deserted hotels, piers and dramatic and terrifying clouds: beautiful but ominous images with a high David Lynch twist. "Moments before the Flood" is a photography of waiting. Carl De Keyzer portrays the uncanny of the vague and uncertain, with a masterful eye for beauty and an unparalleled sense of irony.
This book was published on the occasion of the 'Moments before the flood' exhibition in Ostend, Belgium, 17 May-26 August 2012
boek
Keywords: De Keyzer, Carl